2016
DOI: 10.1007/s11743-016-1798-7
|View full text |Cite
|
Sign up to set email alerts
|

Tetraalkylammonium Ionic Liquids as Dual Solvents–Catalysts for Direct Synthesis of Sugar Fatty Acid Esters

Abstract: As nonionic surfactants derived from naturally renewable resources such as sugars and fatty acids, sugar fatty acid esters have been widely utilized in food, cosmetic and pharmaceutical industries. Our present study has demonstrated that the inexpensive and halogen-free tetraalkylammonium salts (e.g., [Bu 4 N][Ac], [Et 4 N][Ac] and [Me 4 N][Ac]) can act as dual solvents-catalysts for regioselective acylation to produce glucose laurate. This non-enzymatic synthesis can proceed under mild conditions with high sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Both Lipozyme TLIM and Novozym 435 are able to catalyze the synthesis of glucose laurate, either through transesterification of glucose and vinyl laurate or through esterification of methyl glucoside and lauric acid. The product was identified as a mono-ester [27]. As no systematic research has been carried out regarding the use of IL or DES as solvents for these two specific reactions catalyzed by the two enzymes, respectively (Reactions 1 and 2 in Scheme 1), 14 different ILs were screened for the two reactions, and 14 DESs for the second reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Both Lipozyme TLIM and Novozym 435 are able to catalyze the synthesis of glucose laurate, either through transesterification of glucose and vinyl laurate or through esterification of methyl glucoside and lauric acid. The product was identified as a mono-ester [27]. As no systematic research has been carried out regarding the use of IL or DES as solvents for these two specific reactions catalyzed by the two enzymes, respectively (Reactions 1 and 2 in Scheme 1), 14 different ILs were screened for the two reactions, and 14 DESs for the second reaction.…”
Section: Resultsmentioning
confidence: 99%
“…also report these positive effects in hydrolysis reactions with the use of more hydrophobic protic ionic liquids. The literature has revealed that the performance of these ILs was dependent on both the cation and the anion . In this work, the same anion was studied, varying the cation of the ionic liquid.…”
Section: Resultsmentioning
confidence: 99%
“…Reactions may be performed in the presence or absence of enzymes (Abdulmalek et al, 2012; Yang and Huang, 2012; Findrik et al, 2016). In chemical synthesis, ILs can act as both the catalyst and the solvent of the reaction (Forsyth et al, 2002; Lin et al, 2016). The choice of IL for enzymatic reactions is crucial, to ensure that the enzyme is not deactivated.…”
Section: Ionic Liquids For the Synthesis Of Sfaesmentioning
confidence: 99%
“…Lin et al described the synthesis of glucose monolaurate in ILs (Lin et al, 2015, 2016) with and without the use of enzymes. They studied the impact of the IL on SFAEs synthesis by enzymatic processes and they showed that better ester formation was achieved with ILs with a hydrophobic cation and a hydrophilic anion, such as [HMIm][TfO].…”
Section: Ionic Liquids For the Synthesis Of Sfaesmentioning
confidence: 99%